The Understanding of Religious and Multicultural Culture in Manado City Society from Maqâshid Al-Syarî`ah Perspective - Darwis, Rizal; Abdullah, Abdullah; Wibawa, Nazar Husain Hadi Pranata; Rahim, Arhjayati (Madania: Jurnal Kajian Keislaman, 2022)
Religion and culture are two inseparable things. Grounded religious values require traditions and culture that develop in society. This article aims to analyze the religious and cultural understanding of multiculturalism in the people of Manado City. This research is a qualitative descriptive study with data sources coming from the literature and interviews. The data were analyzed using the maqâshid al-syarî`ah approach. The results of the study show that the city of Manado as an area with a multicultural population strongly adheres to the religious understanding that every religion in principle loves, respects, and respects each other. The philosophy of sitou timou tumou tou, torang samua basudara, mapalus, democracy, anti-discrimination and friendship are believed and guided in carrying out all social activities in Manado society. If viewed from the perspective of maqâshid al-syarî`ah, then it is included in the category of maslahat al-‘ummah. Agama dan budaya adalah dua hal yang tidak terpisahkan. Nilai-nilai agama yang membumi membutuhkan tradisi dan budaya yang berkembang di masyarakat. Artikel ini bertujuan menganalisis paham keagamaan dan budaya multikulturalis pada masyarakat Kota Manado. Penelitian ini merupakan penelitian deskriptif kualitatif dengan sumber data berasal dari kepustakaan dan hasil wawancara. Data dianalisis dengan menggunakan pendekatan maqashid al-syariah. Hasil penelitian menujukkan bahwa Kota Manado sebagai daerah yang berpenduduk multikulturalis sangat berpegang pada pemahaman keagamaan bahwa setiap agama pada prinsipnya saling menyayangi, saling menghormati dan saling menghargai. Falsafah sitou timou tumou tou, torang samua basudara, mapalus, demokrasi, antidiskriminasi dan silaturrahim diyakini dan dipedomani dalam melakukan segala aktifitas sosial dalam masyarakat Manado. Jika ditinjau dari perspektif maqâshid al-syarî`ah, maka masuk dalam kategori maslahat al-‘ummah.